History of Health Professional Education in Nepal - Dixit, Hemang (Journal of Kathmandu Medical College, 2018)
The introduction of Western medicine in Nepal took place during Jung Bahadur’s time as Prime Minister and was slowly disseminated during the tenure of subsequent Rana Prime Ministers Bir, Chandra, Bhim and Joodha. The provision of healthcare in the country was taken as a form of charity provided to the people by the rulers. Whilst the first two government hospitals were started at Kathmandu and Birgunj, others followed as would be rulers were banished to places such as Dhankuta, Tansen or Doti. It was only after the dawn of democracy in 1950 that the Department of Health Services was established. During the past 67 years more hospitals and academic centres for teaching health sciences have come up in different parts of Nepal. Strides have made in the delivery of health care and health sciences education. Much more needs still to be done. Journal of Kathmandu Medical College, Vol. 6, No. 4, Issue 22, Oct.-Dec., 2017, Page: 161-166